Analysis of the Significant Increase of Gender-Based Violence During the Covid-19 Pandemic in the Conflict Zone: the Case of Afghanistan - Maretha Syawallin Umarach; Derina Faslig Silitonga; Humairah Muljabar (Universitas Muhammadiyah Yogyakarta, 2022)
Since it was recorded for the first time in Wuhan, China, at the end of 2019, the number of cases of coronavirus infections around the world has been increasing every day. WHO further declared COVID-19 a global pandemic. This pandemic certainly has direct implications for the country's condition, especially concerning issues of women and children. As one of the worst-performing countries in providing gender-based protection, Afghanistan has shown a significant increase in the number of gender-based physical, sexual, and psychological violence during the pandemic. By applying the structural violence and neopatriarchy approaches, this article conducted an in-depth analysis of the problem formulation of why Afghanistan experienced a significant increase in cases of gender-based violence (GBV) during the COVID-19 pandemic. The research results revealed that the patriarchal culture rooted in the constitution, competition in the legal system, and erosion in government institutions are some of the structural factors that have led to a significant increase in the number of gender-based violence in Afghanistan during the COVID-19 pandemic. The above factors have also caused several policies passed by the government during the pandemic that severely discriminated against women and children.